Human iPSC-Derived Neuronal Cells From CTBP1-Mutated Patients Reveal Altered Expression of Neurodevelopmental Gene Networks - Vijayalingam, S.; Ezekiel, Uthayashanker R.; Xu, Fenglian; Subramanian, T.; Geerling, Elizabeth; Hoelscher, Brittany; San, KayKay; Ganapathy, Aravinda; Pemberton, Kyle; Tycksen, Eric; Pinto, Amelia K.; Brien, James D.; et al. (Frontiers in Neuroscience, 2020)
A recurrent de novo mutation in the transcriptional corepressor CTBP1 is associated with neurodevelopmental disabilities in children (Beck et al., 2016; Beck et al., 2019; Sommerville et al., 2017). All reported patients harbor a single recurrent de novo heterozygous missense mutation (p.R342W) within the cofactor recruitment domain of CtBP1. To investigate the transcriptional activity of the pathogenic CTBP1 mutant allele in physiologically relevant human cell models, we generated induced pluripotent stem cells (iPSC) from the dermal fibroblasts derived from patients and normal donors. The transcriptional profiles of the iPSC-derived ‘early’ neurons were determined by RNA-sequencing. Comparison of the RNA-seq data of the neurons from patients and normal donors revealed down regulation of gene networks involved in neurodevelopment, synaptic adhesion and anti-viral (interferon) response. Consistent with the altered gene expression patterns, the patient-derived neurons exhibited morphological and electrophysiological abnormalities, and susceptibility to viral infection. Taken together, our studies using iPSC-derived neuron models provide novel insights into the pathological activities of the CTBP1 p.R342W allele.